Entomological Exploration of Sand Flies in Human Communities Affected by Cutaneous and Visceral Leishmaniasis in El Hajeb Province, Morocco - Karima El-Mouhdi; Mohammed Fekhaoui; Abdelkader Chahlaoui; Smahane Mehanned; Chafika Faraj; Samia Boussaa (The Scientific World Journal)
Sand flies are the exclusive vectors of leishmaniasis. This group of parasitic diseases is a serious public health problem in Morocco. The aim of this study was to investigate the sand fly fauna, mainly the species composition, biodiversity, and seasonal activity of sand flies in El Hajeb in central Morocco. A total of six stations (Aït Naaman, Aït Rbaa, Aït Brahim, Ain Taoujdate, Sidi Mbarek, and Aït Oufella) were studied, five of which had recently recorded cases of leishmaniasis. Sand fly bimonthly captures were carried out using a sticky paper trap in different biotopes from March to December 2019. A total of 14590 adult sand flies were collected. The activity of the sand fly started in April and declined in November. The periods of high abundance were July, September, and November. Morphological identification of sand flies shows the presence of twelve species: Phlebotomus papatasi, P. longicuspis, P. perniciosus, P. sergenti, P. bergeroti, P. alexandri, P. dreyfussi, P. ariasi, Sergentomyia fallax, S. minuta, S. schwetzi, and S. antennata. The analysis showed that species belonging to the genus Phlebotomus were the most dominant (93.3%) and the risk periods were spread during the summer and autumn seasons. The present study provides for the first time information on the species of sand flies in El Hajeb. It, therefore, provides decision makers with an important tool to conduct vector control actions during peak periods in order to limit the transmission of leishmaniasis. A preprint was made available by the research square in the following link: “https://assets.researchsquare.com/files/rs-1409330/v1/dfef7013-0327-4a54-897f-214924a2d950.pdf?c=1646838874.”